The development of a medicinal Nadir glossary through the #Lancsbox 6.0 of wizard software - Sarudin, Anida; Mohamed Redzwan, Husna Faredza; Anuar Tan, Azlini (Academica Press Solutions, 2022)
By investigating the treasures of numerous disciplines found in Malay manuscripts, it is possible to track and study the intellectuality, scholarship, "weltanschauung," and civilization of the Malay traditional practitioners. The advantages of this information can be seen in the field of Malay medicine, which offers a wealth of medical expertise to be used in treatment as an element of preventing and curing disease among the Malay community, and thus becoming an exclusive information medium for the nation, especially the Ministry of Health of Malaysia (MOH) to provide pertinent information related to health and well-being of the people. This main objective of this study is to develop a glossary for the Malay traditional medicinal terminology dataset using the Ethnosemantic-Medical Framework. The methodology of this study uses the corpus software #Lansbox 6.0 developed by Lancaster University as a data collection tool and the Wizard software to transform the dataset for further analysis. Thus, 7 manuscripts from the Malay World's collection of traditional Malay medicine were acquired through the National Library of Malaysia. Through this study, a glossary dataset that provides multipurpose traditional Malay medicinal terminology was developed. The findings of this research can help assist Malaysia's Ministry of Health in meeting the UNESCO's mission to promote manuscripts as the country's intellectual legacy as well as the NKEA's objective in the digital economy of health and medical information.